Internet quota management system - Santhira Rajah, Praveen Raj (Universiti Malaysia Sarawak, UNIMAS, 2005)
This project is developed mainly as a requiremet of the degree that is being pursued. The project is titled Internet Quota Management System (IQMS) serving the purpose of managing Internet access quota for students of the Faculty of Computer Science and Information Technology, Universiti Malaysia Sarawak. The expected outcome of this project is to optimize the Internet speed in campus especially during peak hours which suffer major traffic bottleneck. Upon implementation of this system, it is hoped that the issues concerning slow internet access in campus at least reduced to allow a better and feasible environment for students and staffs to access the Internet in campus.